Temporal development of flood risk considering settlement dynamics and local flood protection measures on catchment scale: an Austrian case study. Issue 3 (2nd July 2016) - Achleitner, Stefan; Huttenlau, Matthias; Winter, Benjamin; Reiss, Julia; Plörer, Manuel; Hofer, Michael
ABSTRACT: With respect to urban development a common practice is to exclude flood-prone areas from further construction for flood safety reasons. Granting exemptions when local flood safety measures are applied is a topic of continued debate. The Ottnager-Redl/Upper Austria case study investigates various future settlement scenarios with or without local flood protection measures (LFPM). In accordance with the legal situation in the Federal Province of Upper Austria, construction permits require flood safety up to a 100-year flood level plus 20 cm. Estimations of potential flood damage in the catchment's residential areas are based on damage functions used to describe the structural vulnerability at an object level. Impacts are simulated with a distributed hydrological and a 2D-hydraulic model, which incorporate future settlement dynamics. In addition to linking losses to return periods, the cumulative damages within design periods are estimated using a Monte-Carlo modelling framework. Event-based and cumulative losses increase with the different settlement scenarios. The LFPM tested visibly reduce the cumulative losses as they are triggered by high-frequency/low-impact events. Considering single events, the positive effects of LFPM, specifically flexible flood barriers, generally vanish when they exceed the design level. Thus, the increased flood risk due to intensified settlement in the flood-prone area cannot be compensated by LFPM.